THE INFLUENCE OF LIVE STREAMING SHOPPING AND CUSTOMER REVIEWS ON PURCHASING DECISIONS ON OVERSIZE FASHION THROUGH THE SHOPEE MARKETPLACE - Salsabila Veronica Setyaningrum; Ni Made Ida Pratiwi; Ayun Maduwinarti (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
Oversize fashion has become a popular trend among users of this e-commerce platform. Various types of oversized fashion products ranging from t-shirts, blouses, tunics, to dresses. Many shop users choose oversize fashion because it is easy to wear, not complicated, not tight on the body and gives a stylish and trendy impression. There is a challenge in creating a balance between style and proportion so that it still looks attractive and not too big. The purpose of this research is to examine live streaming shopping (X1) and customer reviews (X2) on purchasing decisions (Y) for oversized clothes through the Shopee marketplace. Live streaming shopping is becoming an increasingly popular marketing method due to its interativity and ability to display products directly, which helps consumers understand product details and quality. Customer reviews, as a form of previous user reviews, play an important role in building trust and providing relevant information to potential buyers. This research uses quantitative methods, this data is available through an e-questionnaire using g-from which was distributed to 130 respondents who had purchased oversized fashion through Shopee. The hypothesis was tested through multiple linear analysis. The study results show that live streaming shopping has a positive effect on purchasing decisions, showing that the more interesting and informative it is, the higher the consumer's likelihood of making a purchase. Apart from that, customer reviews were found to have a positive and relevant relationship to purchasing decisions. Positive reviews from previous customers can increase the confidence of new consumers and encourage them to make a purchase